Mixed adenocarcinoma and neuroendocrine prostate cancer: a case report - Rittu Hingorani; Jessica Young; Richard Alweis (Greater Baltimore Medical Center, 2014)
Background: Neuroendocrine prostate cancer is rare but lethal. It is one of the most common extra pulmonary manifestations of small cell cancer. Case presentation: Here we present a case report of a 53-year-old male who presents with a mixed adenocarcinoma and neuroendocrine prostate tumor on a background of previously normal prostate-specific antigen (PSA). His initial symptoms prior to diagnosis included decreased urine output and acute kidney injury (AKI). Conclusion: Neuroendocrine tumor does not elevate the PSA level and hence is often a late finding with a poor prognosis. Special staining on histopathogy is required to reveal this diagnosis.